2021
DOI: 10.1101/2021.02.17.431653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human breast milk enhances intestinal mucosal barrier function and innate immunity in a pediatric human enteroid model

Abstract: Breastfeeding has been associated with long lasting health benefits. Nutrients and bioactive components of human breast milk promote cell growth, immune development, and shield the infant gut from insults and microbial threats. The molecular and cellular events involved in these processes are ill defined. We have established human pediatric enteroids and interrogated maternal milk's impact on epithelial cell maturation and function in comparison with commercial infant formula. Colostrum applied apically to ped… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 75 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Other morphological characteristics of infant HIEs such as shorter epithelial cell height and higher proliferation also reflect features of a developing infant intestinal epithelium. Shorter epithelial cell height is described as a marker of intestinal immaturity and has been reported in duodenal biopsies of infants (45) and more recently, duodenal pediatric HIEs (25). Increased proliferation within the intestinal crypt contributes to crypt hyperplasia and is a potential indicator of an immature intestinal epithelium (46).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other morphological characteristics of infant HIEs such as shorter epithelial cell height and higher proliferation also reflect features of a developing infant intestinal epithelium. Shorter epithelial cell height is described as a marker of intestinal immaturity and has been reported in duodenal biopsies of infants (45) and more recently, duodenal pediatric HIEs (25). Increased proliferation within the intestinal crypt contributes to crypt hyperplasia and is a potential indicator of an immature intestinal epithelium (46).…”
Section: Discussionmentioning
confidence: 99%
“…Promising therapies to decrease the risk of NEC involves improving barrier function in the infant gut using growth factors (57,58), breast milk and its bioactives (59), and probiotics (60)(61)(62). Indeed, a previous study using duodenal HIEs from a two-year-old and five-year-old child showed that colostrum enhanced epithelial barrier function and breast milk increased the production of alpha defensin 5 (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations